Pengaruh Locus of Control, Sikap Keuangan, dan Perecanaan Keuangan Terhadap Perilaku Pengelolaan Keuangan Mahasiswa - Alat, Stefanus Febrianto Triano; Sari, Pristin Prima; maulida, Alfiatul (Indonesian Journal Publisher, 2025)
This study aims to empirically examine the influence of locus of control, financial attitudes, and financial planning on students' financial management behavior. Effective financial management is crucial for students as they transition toward financial independence. A quantitative approach was employed, utilizing a survey method with purposive sampling. The sample consisted of 91 students from the Management Study Program at the Faculty of Economics, Sarjanawiyata Tamansiswa University, enrolled between 2021 and 2024. Data were collected through questionnaires and analyzed using Partial Least Squares (PLS) with SmartPLS 3.0. The results indicate that locus of control has a positive and significant impact on financial management behavior, meaning that students with a higher level of financial control exhibit better financial management practices. Similarly, financial attitudes positively influence financial management behavior, suggesting that a more responsible financial mindset leads to improved financial decisions. Furthermore, financial planning significantly affects financial management behavior, emphasizing that structured financial planning enhances students' ability to manage their finances effectively.